(3QSGdI aj Yde GdbHGf hbSeI NWhWgs - (3GdSGehdj , eMeO Hf YHO GdeLjO GdSGehdj GdSYhOj GdTGaYj,J (B961 (3g` s
(3ChdgG (B:s
(3hHYO , agPg QSGdI JTJed Ydi eYQaI Ydhe GdbHGf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B247 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B244s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B1018 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA QjGVjGJ (B- (3bSe (B3 - (3U (B50 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3QjGVI (B86) s
Keywords: (3GdQjGVjGJs